1984
DOI: 10.1136/vr.114.17.421
|View full text |Cite
|
Sign up to set email alerts
|

Application of an automated enzymatic technique for the determination of non-esterified fatty acids in bovine blood

Abstract: An enzymatic method for the measurement of non-esterified fatty acid (NEFA) concentrations in blood was applied to samples from dairy cows. The method was carried out on a discrete analyser and showed considerable savings over other methods, particularly in time. The precision of the method was very high and the accuracy was good within normal concentration ranges when compared with an extraction reference method. Using this enzymatic method, it is possible to measure NEFA concentrations in bovine serum or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Higher values in serum have been attributed to activation of de-esterifying enzymes (e.g., lecithinases) or lipolytic enzymes during clotting or possible EDTA inhibition of the reaction (McGann and Hodson, 1991). In contrast, NEFA concentrations were higher (albeit not significantly) in EDTA plasma compared with serum in sheep (Morris et al, 2002), and in a previous study in 10 dairy cows (Brookes et al, 1984). A reason for the discrepancies between these results and our data is not readily apparent, but could be related to differences in sample handling and processing, because the same analytical technique was used for these 3 studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Higher values in serum have been attributed to activation of de-esterifying enzymes (e.g., lecithinases) or lipolytic enzymes during clotting or possible EDTA inhibition of the reaction (McGann and Hodson, 1991). In contrast, NEFA concentrations were higher (albeit not significantly) in EDTA plasma compared with serum in sheep (Morris et al, 2002), and in a previous study in 10 dairy cows (Brookes et al, 1984). A reason for the discrepancies between these results and our data is not readily apparent, but could be related to differences in sample handling and processing, because the same analytical technique was used for these 3 studies.…”
Section: Discussionmentioning
confidence: 81%
“…The current protocol for blood sampling for NEFA testing is to collect blood into gel and clot activator or serum separator tubes (SST), allow the blood to clot, centrifuge the sample, transfer the serum into another tube, then ship the serum chilled or frozen overnight for analysis (NEFA and Metabolic Profile Sample Handling Guidelines). A previous study in dairy cows showed that NEFA concentrations were slightly higher in EDTA plasma than in serum in 8 of 10 cows (Brookes et al, 1984). However, to our knowledge, there have been no published reports on the effect of other anticoagulants (e.g., heparin), use of SST, or other preanalytical variables, including delayed separation of serum or plasma from cells, storage temperature, and duration of storage, on NEFA and BHBA concentrations in dairy cows.…”
Section: Introductionmentioning
confidence: 73%
“…4 ) method (Boehringer Mannheim GmbH). Serum was stored at -20" before determination of urea (Boehringer Mannheim GmbH) and nonesterifed fatty acids (NEFA, Brookes et al 1984). Rumen pH, rumen VFA and rumen NH,-N were determined as described previously.…”
Section: Exptmentioning
confidence: 99%
“…1 Other analytical techniques for the separation and quantitation of various saturated and unsaturated free fatty acids have been described. 24,36,40,41 In addition to the above techniques, a number of enzymatic methods 4,8,16,17,22 for the colorimetric detection of NEFA in serum/plasma are now available including a commercially available kit a (''NEFA C'' Kit). This latter technique involves conversion of NEFA to their corresponding enoyl-Coenzyme A (CoA) products with generation of hydrogen peroxide (H 2 O 2 ; Fig.…”
mentioning
confidence: 99%